Exploring the catalytic function and active sites of a novel C-glycosyltransferase from Anemarrhena asphodeloides - Jia Huang; Yaru She; Jingyang Yue; Yidu Chen; Yu Li; Jing Li; Yonger Hu; Deying Yang; Jiabo Chen; Lu Yang; Zhongqiu Liu; Ruibo Wu; et al. (Synthetic and Systems Biotechnology, 2022)
Anemarrhena asphodeloides is an immensely popular medicinal herb in China, which contains an abundant of mangiferin. As an important bioactive xanthone C-glycoside, mangiferin possesses a variety of pharmacological activities and is derived from the cyclization reaction of a benzophenone C-glycoside (maclurin). Biosynthetically, C-glycosyltransferases are critical for the formation of benzophenone C-glycosides. However, the benzophenone C-glycosyltransferases from Anemarrhena asphodeloides have not been discovered. Herein, a promiscuous C-glycosyltransferase (AaCGT) was identified from Anemarrhena asphodeloides. It was able to catalyze efficiently mono-C-glycosylation of benzophenone, together with di-C-glycosylation of dihydrochalcone. It also exhibited the weak O-glycosylation or potent S-glycosylation capacities toward 12 other types of flavonoid scaffolds and a simple aromatic compound with –SH group. Homology modeling and mutagenesis experiments revealed that the glycosylation reaction of AaCGT was initiated by the conserved residue H23 as the catalytic base. Three critical residues H356, W359 and D380 were involved in the recognition of sugar donor through hydrogen-bonding interactions. In particular, the double mutant of F94W/L378M led to an unexpected enzymatic conversion of mono-C- to di-C-glycosylation. This study highlights the important value of AaCGT as a potential biocatalyst for efficiently synthesizing high-value C-glycosides.